(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objectives: This study aimed to investigate the molecular prevalence and species distribution of feline hemoplasmas—Mycoplasma haemofelis (Mhf) and “Candidatus Mycoplasma haemominutum” (CMhm)—in domestic cats in southern Vietnam. The 16S rRNA gene was used as a molecular marker for this research. To assess their clinical relevance, the blood and chemical profiles of the infected cats were also examined. Materials and Methods: We collected a total of 68 blood samples from domestic cats brought to the Veterinary Teaching Clinic, Faculty of Veterinary Medicine, Can Tho University, Vietnam. To screen for hemoplasma, genomic deoxyribonucleic acid was extracted, and conventional polymerase chain reaction (PCR) was used to target the 16S rRNA gene. We sequenced the positive samples and then used nucleotide BLAST to identify the species. The simulated hematological and biochemical data, including hematocrit, alanine aminotransferase (ALT), and blood urea nitrogen (BUN), were reviewed to support clinical interpretation. Results: In this study, five of the 68 samples (7.35%) tested positive for feline hemoplasmas. Two of the samples were identified as M. haemofelis, while three were classified as “Candidatus Mycoplasma haemominutum”. Cats infected with Mhf exhibited normocytic normochromic anemia, accompanied by increased ALT levels and a slight elevation in BUN. These findings suggest that the infection affects the whole body. In contrast, cats that tested positive for CMhm showed no clinical symptoms, and their blood and biochemical tests were normal. Conclusion: This study confirms presence of both Mhf and CMhm in domestic catsin Southern Vietnam. Although CMhm is generally considered low virulence, the hematobiochemical alterations observed in Mhf-positive cats warrant attention. PCR targeting the 16S rRNA gene proves effective for diagnosis and epidemiological surveillance. J. Adv. Vet. Anim. Res., 12(4): 1297–1304, December 2025 http://doi.org/10.5455/javar.2025.l990